Improvements in peripheral vascular function with vitamin D treatment in deficient adolescents with type 1 diabetes. Issue 3 (23rd October 2017) - Deda, Livia; Yeshayahu, Yonatan; Sud, Shama; Cuerden, Meaghan; Cherney, David ZI; Sochett, Etienne B; Mahmud, Farid H
Abstract : Background: Vitamin D (VitD) deficiency is prevalent in adolescents with type 1 diabetes (T1D) and is associated with diabetes‐related vascular complications in adulthood. The objective of this clinical trial was to assess VitD treatment on endothelial function (EF) and markers of renal inflammation, in this patient group. Methods: Adolescents with T1D with suboptimal levels of VitD (<37.5 nmol/L) were treated for 12 to 24 weeks with a VitD analog (VitD3 ) at doses of 1000 or 2000 IU daily. The primary end‐point assessed the change in reactive hyperemia index (lnRHI), a measure of EF. Secondary end‐points included changes in blood pressure, lipid profile, HbA1c and albumin creatinine ratio (ACR). Urinary cytokine/chemokine inflammatory profile was also assessed in a subset of subjects posttreatment. Results: Two hundred and seventy‐one subjects were screened for VitD status and 31 VitD deficient subjects with a mean age of 15.7 ± 1.4 years were enrolled and completed the study. Mean 25‐OH‐VitD levels significantly increased (33.0 ± 12.8 vs 67.0 ± 23.2 nmol/L, P  < .01) with a significant improvement in EF following VitD supplementation (lnRHI 0.58 ± 0.20 vs 0.68 ± 0.21, P  = .03). VitD supplementation did not significantly impact systolic blood pressure/diastolic blood pressure (SBP/DBP), lipids, HbA1c and ACR and no adverse effects were seen. Several urinary inflammatory cytokines/chemokines: MCP‐3 ( P  < .01), epidermal growth factor (EGF) ( P  < .01) tumor necrosis factor β (TNFβ) ( P  = .01), interleukin‐10 (IL‐10) ( P  = .01), also significantly decreased post‐VitD‐treatment. Conclusions: Treatment with VitD was associated with an improvement in EF and reduced expression of urinary inflammatory markers in adolescents with T1D. This data is suggestive of an additional benefit of VitD supplementation on early markers of microvascular complications.